Special legal regimes for attraction private investment and modern technologies to the development of territories - A. N. Shvetsov (Контуры глобальных трансформаций: политика, экономика, право, 2015)
The article analyzes the practice of using special legal regimes of doing business to attract private investments and new technologies in the economy of the country and its regions. The author describes the characteristic features and evaluates the efficiency and effectiveness of the tools such as special economic zones, zones of territorial development, clusters, and territories of priority development. The author characterizes key problems and recommends measures to improve the mechanisms of territorial development based on the specific legal regimes.